A major myna problem; invasive predator removal benefits female survival and population growth of a translocated island endemic - Thomas J. Brown; Max Hellicar; Wilna Accouche; Jildou van der Woude; Hannah L. Dugdale; Jan Komdeur; David S. Richardson (Global Ecology and Conservation, 2023)
Invasive predators are a major driver of extinctions and continue to threaten native populations worldwide. Island eradications of (mostly mammalian) invasive predators have facilitated the reestablishment of numerous island-endemic populations. Other invasive taxa, such as some predatory birds, could pose a more persistent threat due to their ability to fly and actively re-invade even remote and isolated islands. However, the impact of invasive predatory birds has been largely overlooked. We report on a novel sex-specific impact of an invasive-nest predator, the common myna (Acridotheres tristis), on a reintroduced population of Seychelles warblers (Acrocephalus sechellensis); translocated from Cousin Island to Denis Island in 2004. Regular post-translocation monitoring revealed that female mortality was 20 % higher than males, leading to a 60–70 % male-biased population sex-ratio between 2005 and 2015. This was attributed to common mynas inflicting severe injuries to incubating female Seychelles warblers while attempting to prey upon eggs in their nests. These effects likely contributed to the slower-than-expected population growth observed (relative to previous translocations of Seychelles warblers to other islands) over the same period. An eradication programme beginning in 2011 removed all common mynas from Denis by 2015. Subsequently, we observed a balancing of sex-specific survival and the population sex-ratio of Seychelles warblers and, consequently, accelerated population growth. This study demonstrates the importance of assessing the threat posed by all invasive taxa (not just mammals) to island conservation. Furthermore, we show how extended monitoring is needed to identify problems, and develop solutions, post-translocation.